Neuregulin-1, a potential therapeutic target for cardiac repair - Wang, Yan; Wei, Jianliang; Zhang, Peng; Zhang, Xin; Wang, Yifei; Chen, Wenjing; Zhao, Yanan; Cui, Xiangning (Frontiers in Pharmacology, 2022)
Neuregulin-1 (NRG1) is an effective cardiomyocyte proliferation stimulator, secreted by vascular endothelial cells and acts on the cardiovascular system, involved not only in the regulation of cellular hypertrophic growth, proliferation, differentiation, apoptotic life processes and neural signaling, but also in the formation of a signaling cascade through the NRG1 / ErbB pathway to regulate cellular inflammation, oxidative stress, necrotizing apoptosis, myocardial fibrosis and other pathological processes, improving from multiple aspects. It can improve the myocardial microenvironment to promote cardiac repair and become a potential therapeutic target for cardiovascular diseases. Numerous in vitro and animal experiments have shown that NRG1 plays an important role in the pathophysiology of cardiovascular diseases such as atherosclerosis, myocardial infarction (MI), ischemia/reperfusion (I/R), heart failure (HF), and cardiomyopathy. Here, we summarize recent research advances on the molecular mechanisms of NRG1, elucidate the contribution of NRG1 to cardiovascular disease, discuss therapeutic approaches targeting NRG1 associated with cardiovascular disease, and highlight areas for future research.